La importancia de las competencias en la educación superior - De Faria Campos, Edison (2010)
In this article we analyze the importance of the competencies in the higher education system, and describe four important projects in this area: DeSeCo, Tuning Europe, Tuning Latin America and the 6x4 UEALC.